Dynamic Influence of Near-Source Seismic Ground Motion on Underground Mine Working Stability Using Time-Frequency Analysis - Adam Lurka; Grzegorz Mutke; Piotr Małkowski (Shock and Vibration)
Peak particle velocity parameter is very useful in assessing underground mine working stability. Its application is widespread and requires additional analysis of the dominant frequency of the seismic signal. In order to properly analyze the velocity amplitudes of strong ground motions generated from seismic sources, time-frequency properties of near-source seismic signals in underground mines should be quantified. Using numerical calculations, the continuous wavelet transform (CWT) of the recorded near-source seismic signals in three perpendicular directions was obtained to characterize its time-frequency properties. The properties of recorded strong ground motion velocity seismograms for two high energy seismic events and two blasts from two underground coal mines in Poland have been extracted with the use of continuous wavelet transform spectrograms showing the duration time of each frequency group. Assuming a constant peak particle velocity amplitude on the analyzed seismograms, the duration time of each frequency group starts to play a key role. The longer the duration time of the lower frequency group is on the CWT spectrogram, the more the damaging effect on underground mining excavations can be observed. Varying bandwidths of dominant frequencies in separate time intervals for the analyzed seismic signals have had significantly different influence on the potentially damaging effect on underground mining excavations.